Validating clinical practice guidelines for the management of children with non-blanching rashes in the UK (PiC): a prospective, multicentre cohort study. Issue 4 (April 2021) - Waterfield, Thomas; Maney, Juli-Ann; Fairley, Derek; Lyttle, Mark D; McKenna, James P; Roland, Damian; Corr, Michael; McFetridge, Lisa; Mitchell, Hannah; Woolfall, Kerry; Lynn, Fiona; Patenall, Bethany; et al.
Summary: Background: No previous studies have validated current clinical practice guidelines for the management of non-blanching rashes in children who have received meningococcal B and C vaccinations. The aim of this study was to evaluate the performance of existing clinical practice guidelines in the diagnosis of invasive meningococcal disease in children presenting with a fever and non-blanching rash in the UK. Methods: The Petechiae in Children (PiC) study was a prospective, multicentre cohort study involving children (aged <18 years) presenting to 37 paediatric emergency departments in the UK with a fever (≥38°C) and a new-onset non-blanching rash or features suggestive of meningococcal infection. Children with pre-existing haematological conditions (ie, haematological malignancy, idiopathic thrombocytopenic purpura, or coagulopathy) or an existing diagnosis of Henoch-Schonlein purpura were excluded. Invasive meningococcal disease was confirmed by positive culture or a quantitative PCR test for Neisseria meningitidis from either blood or cerebrospinal fluid samples. The primary outcome was the performance of six tailored clinical practice guidelines from participating centres (London, Nottingham, Newcastle–Birmingham–Liverpool, Glasgow, Chester, and Bristol) and two clinical practice guidelines from the National Institutes for Health and Care Excellence (NICE; CG102 and NG51) in identifying children with invasive meningococcal disease, assessed by the sensitivity and specificity of each clinical practice guideline. This study is registered with ClinicalTrials.gov, NCT03378258 . Findings: Between Nov 9, 2017, and June 30, 2019, 1513 patients were screened, of whom 1329 were eligible and were included in the analysis. The median age of patients was 24 months (IQR 12–48). 1137 (86%) of 1329 patients had a blood test and 596 (45%) received parenteral antibiotics. 19 (1%) patients had confirmed meningococcal disease. All eight clinical practice guidelines had a sensitivity of 1·00 (95% CI 0·82–1·00) for identifying meningococcal disease. The specificities of NICE guidelines CG102 (0·01 [95% CI 0·01–0·02]) and NG51 (0·00 [0·00–0·00]) for identifying meningococcal disease were significantly lower than that of tailored clinical practice guidelines (p<0·0001). The best performing clinical practice guidelines for identifying meningococcal disease were the London (specificity 0·36 [0·34–0·39]) and Nottingham (0·34 [0·32–0·37]) clinical practice guidelines. Interpretation: Invasive meningococcal disease is a rare cause of non-blanching rashes in children presenting to the emergency department in the UK. Current NICE guidelines perform poorly when compared with tailored clinical practice guidelines. These findings suggest that UK national guidance could be improved by shifting towards a tailored approach. Funding: Public Health Agency.